Defective B cell responses in the absence of SH2D1A - Massimo Morra; Robert A. Barrington; Ana Clara Abadía‐Molina; Susumo Okamoto; Aimée Julien; Charles Gullo; Anuj Kalsy; Matthew Edwards; Gang Chen; Rosanne Spolski; Warren J. Leonard; Brigitte T. Huber; et al. (2005)
More than half of patients with X-linked lympho-proliferative disease, which is caused by a defect in the intracellular adapter protein SH2D1A, suffer from an extreme susceptibility to Epstein-Barr virus. One-third of these patients, however, develop dysgammaglobulenemia without an episode of severe mononucleosis. Here we show that in SH2D1A(-/-) mice, both primary and secondary responses of all Ig subclasses are severely impaired in response to specific antigens. Because germinal centers were absent in SH2D1A(-/-) mice upon primary immunization, and because SH2D1A was detectable in wt germinal center B cells, we examined whether SH2D1A(-/-) B cell functions were impaired. Using the adoptive cotransfer of B lymphocytes from hapten-primed SH2D1A(-/-) mice with CD4(+) T cells from primed wt mice into irradiated wt mice provided evidence that signal transduction events controlled by SH2D1A are essential for B cell activities resulting in antigen specific IgG production. Defects in naive SH2D1A(-/-) B cells became evident upon cotransfer with non-primed wt CD4(+) cells into Rag2(-/-) recipients. Thus, both defective T and B cells exist in the absence of SH2D1A, which may explain the progressive dysgammaglobulinemia in a subset of X-linked lympho-proliferative disease patients without involvement of Epstein-Barr virus.